On the Impact of Distance Metrics in Instance-Based Learning Algorithms - Lopes, Noel (2016)
In this paper we analyze the impact of distinct distance metrics in instance-based learning algorithms. In particular, we look at the well-known 1-Nearest Neighbor (NN) algorithm and the Incremental Hypersphere Classifier (IHC) algorithm, which proved to be efficient in large-scale recognition problems and online learning. We provide a detailed empirical evaluation on fifteen datasets with several sizes and dimensionality. We then statistically show that the Euclidean and Manhattan metrics significantly yield good results in a wide range of problems. However, grid-search like methods are often desirable to determine the best matching metric depending on the problem and algorithm.